The Effect of Technology Acceptance Model and Internet Usage Factory to Financial Literacy of Active User of Financial Technology Application Among Millennial Generation : English - Livia Marsha Sarengat; Putu Anom Mahadwartha (Jurnal Bisnis dan Keuangan, 2021)
This experiment examined the effect of Technology Acceptance Model which generated as perceived usefulness and perceived ease of use, and internet usage factor to financial literacy of active user of financial technology application among milenial generation. This experiment is basic research with using quantitative analysis, data of this experiment from results of respondent’s answer in questionnaire and processed with SEM-PLS technique analysis. The result of this experiment will be used for next curriculum development in the future in connected field.